Molecular Characterization and Functional Analysis of Selected Expressed Sequence Tags from Oil Palm Cell Suspension Culture - Le, Vinh Thuc (2009)
A large quantity of Expressed sequence tags (ESTs) are available from various cDNA libraries of oil palm. The information from oil palm EST databases has been utilized to identify several interesting transcripts that are upregulated in cell suspension culture for molecular characterization and functional analysis. The first part of this study was to carry out the molecular characterization of selected ESTs of oil palm cell suspension culture which were Eg583 (Accession number: EU795363), Eg707 (Accession number: FJ196136) and EgHAD (Accession number: FJ196137). The Eg583 sequence is highly similar to an unknown protein from rice. This predicted protein might be a transcription factor due to the presence of SIN3 domain and motifs of casein kinase II phosphorylation. The expression of this gene was not detectable in all tested tissues. This gene might be a member of a multigene family in the oil palm genome. The Eg707 sequence is highly similar to an unknown protein from Arabidopsis and might be a putative nuclear protein. Its amino acid sequence contains a Ald-Xan-dh-C2 domain that may be involved in ABA biosynthesis. Eg707 might be present as a single copy gene in the oil palm genome and its transcripts were highly expressed in tissue cultured materials compared to vegetative tissues. Eg707 might have a role during oil palm somatic embryogenesis or at very early stage of embryo development. The EgHAD sequence is similar to a putative haloacid dehalogenase (HAD) superfamily hydrolase from monocots and phosphate hydrolase from dicots. However, the phylogenetic relationship of EgHAD is closer to monocots than dicots. EgHAD might be a member of a multigene family gene in the oil palm genome. It was highly expressed in leaves and meristem but lower expression was found in roots, female flowers, non-embryogenic and embryogenic calli in comparison to the oil palm cell suspension culture. Functional analysis was carried out in rice by over-expressing Eg707 and EgHAD, driven by a constitutive double Cauliflower Mosaic Virus 35S promoter. The constructs were made using the gateway technology with clonase (Invitrogen, USA). Transgenic plants over-expressing Eg707 protein had small sized, rolled and erect leaves, less tillers, empty seeds and higher total chlorophyll content. The phonotypes of these and the presence of Xan-dh-C2 domain in Eg707 protein, strongly suggest its involvement in ABA biosynthesis, particularly during somatic embryogenesis. Functional analysis of Eg707 through RNAi-mediated gene silencing was unsuccessful since the T1 seeds failed to germinate. Over-expression of EgHAD gene in rice produced more lateral roots and tillers than the wild type plants. However, it also reduced plant size, produced empty seeds and many tiny seeds which were not found in wild type plants. The suppression of the EgHAD orthologues in rice did not show any changes in the phenotype. EgHAD might be a metabolic protein involved in phosphate starvation mechanism and its expression might be necessary for seed germination.